Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 1-6 - Cumulative Review: 69

Answer

$f^{-1}(x) = \frac{x-12}{3}$

Work Step by Step

$f(x) = 3x+12$ Let $f(x) = y$ $y = 3x+12$ Swap $x$ and $y$ and then solve for $y$. $x = 3y + 12$ $x-12 = 3y$ $y = \frac{x-12}{3}$ $f^{-1}(x) = \frac{x-12}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.